Performance of M&A and Their Impact on The Acquirers: The Case of Mittal Arcelor Merger - Madan, Kanika (2007)
From the past few decades, Mergers and Acquisitions (M&A) have dominated the environment in which the companies operate. Various researches have also been carried out where the main focus of the study is on the abnormal returns of the acquirers of the firm after the merger.The results have revealed that on average,the returns to the target companies are positive and that they gain from mergers.However,the bidder returns may be zero or negative, but it still remains a puzzle if they gain from mergers in the long-run.